INSTRUMEN GAYA BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Astuti Astuti; Yonarlianto Tembang; St Budi Waluya; M Asikin (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The research aims to measure the feasibility and reliability of the mathematics learning style instrument. The initial stage is the preparation of the instrument, followed by logical validity testing and trials. Instrument trials were carried out in class IIIB of an elementary school in Ungaran, Central Java with 36 respondents. The validity test was continued using the Pearson product moment formula using the Office Excel program with valid criteria if   rxy>rtable at a significant level of 5%. Based on the validity test, out of 30 instruments, 21 were valid. Reliability test using Alpha Cronbach formula calculation using Office Excel. The results of the reliability test were r11=0,6497, rtable=0,3202, it was concluded that the instrument had a fairly good level of reliability.